'A Living Dog Is Better Than A Dead Lion', Bull Dog Pluck v. Feline Craft. - Mecham, William, 1853-1902; Merry, Tom (My University, 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Bible. O.T. Ecclesiastes -- Quotations; John Bull (Symbolic character); Great Britain -- Politics and government -- 1837-1901